Plot & structure : techniques and exercises for crafting a plot that grips readers from start to finish - Bell, James Scott (Cincinnati, Ohio : Writer's Digest Books, 2004)
Offers writers practical guidance on how to create a strong, interesting plot for their stories, with tips, plotting diagrams and charts, brainstorming techniques, exercises, structure models, and other resources.
Putting the big lie to sleep -- What's a plot, anyway? -- Structure: what holds your plot together -- How to explode with plot ideas -- Beginning strong -- Middles -- Endings -- Scenes -- Complex plots -- The character arc in plot -- Plotting systems -- Revising your plot -- Plot patterns -- Common plot problems and cures -- Tips and tools for plot and structure -- Checklist: critical points -- Creating your own back cover copy.
Includes index.
Keywords: Plots (Drama, novel, etc.); Fiction -- Authorship; Fiction -- Authorship; Plots (Drama, novel, etc.)